Unique Roles for Streptococcus pneumoniae Phosphodiesterase 2 in Cyclic di-AMP Catabolism and Macrophage Responses - Wooten, Alicia K.; Shenoy, Anukul T.; Arafa, Emad I.; Akiyama, Hisashi; Martin, Ian M. C.; Jones, Matthew R.; Quinton, Lee J.; Gummuluru, Suryaram; Bai, Guangchun; Mizgerd, Joseph P. (Frontiers in Immunology, 2020)
Cyclic di-AMP (c-di-AMP) is an important signaling molecule between and within pneumococci, and as a uniquely prokaryotic product it can be recognized by mammalian cells as a danger signal that triggers innate immunity. Roles of c-di-AMP in directing host responses during pneumococcal infection are only beginning to be defined. We hypothesized that pneumococci with defective c-di-AMP catabolism due to phosphodiesterase deletions could illuminate roles of c-di-AMP in mediating host responses to pneumococcal infection. Pneumococci deficient in phosphodiesterase 2 (Pde2) stimulated a rapid induction of interferon beta (IFNbeta) expression that was exaggerated in comparison to that induced by wild type bacteria or bacteria deficient in phosphodiesterase 1. This IFNbeta burst was elicited in mouse and human macrophage-like cell lines as well as in primary alveolar macrophages collected from mice with pneumococcal pneumonia. Macrophage hyperactivation by Pde2-deficient pneumococci led to rapid cell death. STING and cGAS were essential for the excessive IFNbeta induction, which also required phagocytosis of bacteria and triggered the phosphorylation of IRF3 and IRF7 transcription factors. The select effects of Pde2 deletion were products of a unique role of this enzyme in c-di-AMP catabolism when pneumococci were grown on solid substrate conditions designed to enhance virulence. Because pneumococci with elevated c-di-AMP drive aberrant innate immune responses from macrophages involving hyperactivation of STING, excessive IFNbeta expression, and rapid cytotoxicity, we surmise that c-di-AMP is pivotal for directing innate immunity and host-pathogen interactions during pneumococcal pneumonia.